THE DEVELOPMENT OF THE MARKET PRODUCTION OF CEREALS IN SERBIA: EXAMPLE WHEAT AND CORN - Stevanović, Simo; Đorović, Мilutin; Milanović, Milan (Economics of Agriculture, 2012)
In the paper, the tendencies in the development of wheat and corn production in the time period from 1976 to 2010 are researched, with a focus on the cluster analysis of the market production of these products per districts in Serbia in 2009. On the basis of more important available land capacities, the volume of production and scope of economic development, the I-distance method is used to rank the districts. The ranking of the districts according to the analysed characteristics is conducted on the basis of the median value of data per municipalities. For each of the mentioned groups of characteristics, the I-distance is used to rank the districts from 1 to 25, Rank 1 being the best and Rank 25 the worst. The similarities of the districts according to the analysed characteristics are accounted for by a complete link method of a hierarchical cluster analysis and the results are represented by a dendrogram and a cartogram. Apart from favourable conditions (land, climate, and so on), producers traditional habits have to the greatest extent had an impact on the unjustifably high presence of wheat and corn in the structure of crop production. That, to a great extent, has had an influence on the high marketability of the production of wheat and corn in Serbia as well.